Das Nordböhmische Braunkohlenbecken - Förster, Horst (ERDKUNDE, 1971)
This paper seeks to outline some of the most important basic factors in the contemporary economic structure of the North Bohemian brown coal basin. Investigations were carried out into the factors of mining economics, of primary importance to economic potential, and into the structural and functional development tendencies of the constituent areas. The important effects of economic activity on the geographical environment, on settlement structure and on the social structure of the population have only been dealt with peripherally. Following an introduction to the natural divisions of the area and the exploitation potential of the natural resources, the phases in regional historical development of the various types of production are described. Conditions of mining technology, the general state of technology, measures of economic policy and conjunctions of political events caused the gigantic changes in structure and function which the North Bohemian brown coal basin has undergone in the last hundred years. Especially after 1945, decisive changes occurred as the principles of the socialist economy were carried through into the mining industry. The great importance of brown coal as a source of energy for the entire economy of the CSSR resulted, as production expanded, in North Bohemia becoming one of the most important industrial centres of the Republic.